Change leadership and public sector organizational change: examining the interactions of transformational leadership style and red tape - Voet, Joris van der (2016)
The implementation of organizational change is a considerable challenge for public organizations. Recent studies have highlighted the importance of leadership in change processes in public organizations, but limited empirical evidence exists. Moreover, the contribution of change leadership in organizational change is likely to be dependent on the particular characteristics of public organizations. This study concerns the relationship between direct supervisor's change leadership and the commitment to change of change recipients, and examines to what extent this relationship is related to the bureaucratic features that often characterize public organizations. The findings indicate that change leadership contributes to change recipient's commitment to change by providing high-quality change communication and stimulating employee participation in the implementation of change. However, the findings also indicate that red tape perceptions of change recipients and a low reliance on a transformational leadership style impede the potential of change leadership to bring about employee participation in the implementation of change. - Reproduced.
Keywords: Organizational Change; Leadership